Penerapan Arsitektur Perilaku Pada Perencanaan Asrama Mahasiswa Di Kota Sengkang Kabupaten Wajo - Satriandika, Baso; Said, Ratriana; Nursyam, Nursyam (TIMPALAJA : Architecture Student Journals, 2022)
Planning for student dormitories is a means of fulfilling residential needs for students in Sengkang city, Wajo district. As for this design research using the method of literature study and field studies with in-depth interview techniques, observation and documentation. The object of this research focuses on the Puanrimagalatung University and the Lamaddukeleng Campus which are close together. The architectural approach used in planning student dormitories uses behavioral architecture with the aim of regulating behavior and minimizing deviant behavior in student building users. The design results obtained are able to provide comfort in terms of student accessibility to campus and the infrastructure that supports the lives of its residents. In addition, this dormitory planning also pays attention to meeting the needs of dormitory residents by providing supporting facilities in the hostel environment.